A Jurassic gliding euharamiyidan mammal with an ear of five auditory bones - Han, Gang; Mao, Fangyuan; Bi, Shundong; Wang, Yuanqing; Meng, Jin (Nature (London), 2017)
Gliding is a distinctive locomotion type that has been identified in only three mammal species from the Mesozoic era. Here we describe another Jurassic glider that belongs to the euharamiyidan mammals and shows hair details on its gliding membrane that are highly similar to those of extant gliding mammals. This species possesses a five-boned auditory apparatus consisting of the stapes, incus, malleus, ectotympanic and surangular, representing, to our knowledge, the earliest known definitive mammalian middle ear. The surangular has not been previously identified in any mammalian middle ear, and the morphology of each auditory bone differs from those of known mammals and their kin. We conclude that gliding locomotion was probably common in euharamiyidans, which lends support to idea that there was a major adaptive radiation of mammals in the mid-Jurassic period. The acquisition of the auditory bones in euharamiyidans was related to the formation of the dentary-squamosal jaw joint, which allows a posterior chewing movement, and must have evolved independently from the middle ear structures of monotremes and therian mammals. The fossil of a gliding mammal from the Jurassic period sheds light on both the evolution of gliding and the development of the middle ear, as it has a previously unseen five-ossicle auditory system. Ancient glider lends an ear bone or two The haramiyids were a group of mammals living in the age of dinosaurs that seem to have had a penchant for gliding, rather like flying squirrels of today. Two newly described species of gliding haramiyids were presented recently and now Jin Meng and colleagues follow with another. The new species lived in China in the Jurassic period between 164 and 159 million years ago and shows many intriguing features in addition to its adaptations for gliding. Its middle ear, for example, represents an interesting way-station in the evolution of the mammalian middle ear, which today is made up of three ossicles (the stapes, malleus and incus). It appears that the surangular of the jaw and the ectotympanic of the skull joined the trio of bones to form a hitherto unseen five-ossicle system.